A Comparative Study of Coconut Shell and Melinjo Shell as Carbon Sources for Bio-Briquette Production - Augustina, Nadya; Manfaati, Rintis; Rizky, Alfiani; Yusuf, Yusmardhany; Adhitasari, Alfiana (Eksergi, 2024)
The aim of this research was to investigate the influence of adding Melinjo shells on the quality and efficiency of charcoal-based bio-briquettes. A combination of coconut shells and Melinjo shells in various ratios was utilized in the study. The briquettes were produced through a carbonization process at a temperature of 300°C for 60 minutes, with tapioca flour used as a binder. Subsequently, the briquettes underwent testing to determine moisture content, ash content, volatile matter, and calorific value. The research findings indicated that all briquettes met the calorific value requirements set by the Indonesian National Standard (SNI), exceeding 5,000 cal/g. The addition of Melinjo shells resulted in a reduction in ash and volatile matter content but also led to a decrease in calorific value. Based on the analysis, the optimal composition obtained was 90 grams of coconut shells and 10 grams of Melinjo shells, producing briquettes with a calorific value of 5,582 cal/g, ash content of 3.76%, and volatile matter content of 6.65%. Therefore, further research is recommended to identify easily combustible components in Melinjo shells to ensure their potential in reducing the amount of ash produced when the briquettes are burned.